Exploring the Benefits and Barriers of QRIS Adoption Among Micro Businesses in North Bogor - Widyawan, Bisma; Barlian, Achmad; Haryanto, Joni; Haddad Bayhaqi, Mohamad (Journal of Accounting and Finance Management, 2024)
This study explores the role of the Indonesian Standard QR Code (QRIS) in enhancing the business outcomes of micro enterprises in North Bogor Subdistrict. While QRIS has been recognized as a crucial technological advancement for promoting financial inclusion, there remains a reluctance among some micro business owners to adopt it. This research utilizes a descriptive qualitative method, including interviews with micro entrepreneurs who do and do not use QRIS, government officials involved in MSME development, and financial institution representatives. The findings reveal that the adoption of QRIS is often driven by its integration with delivery services rather than its potential to boost business performance. Despite some entrepreneurs experiencing benefits from QRIS, a significant gap in understanding its full potential as a payment method persists. For those not using QRIS, reasons include the efficiency of cash transactions, additional costs, and expectations more on government support in promoting their products to achieve business growth.